(untitled) (Journal of Bangladesh Academy of Sciences, 2023)
Jute (Corchorus olitorius) endophytic fungi Grammothele lineata SDL-CO-2015-1 was found to produce epothilone B, a well-reported anticancer compound. Both the genome and RNA-seq data of G. lineata revealed the presence of epothilone gene clusters. In silico mining using NaPDoS (Natural Product Domain Seeker) identified four genes matching with the epothilone gene cluster (Epo D). Epothilone was extracted from the extracellular extract of this fungus using XAD-16 resin. Different analytical techniques including thin layer chromatography (TLC), reverse phase high-performance liquid chromatography (RP-HPLC), and mass spectrometry (MS) were used to identify and characterize epothilone following its extraction. TLC bands were visible at 365 nm for both standard epothilone B and samples with identical Rf values. Extracted epothilone bands from the TLC plate were further purified using RP-HPLC. Using a linear gradient system with methanol and 0.1% formic acid, LC-MS spectroscopy was done with RP-HPLC purified fraction. The monoisotopic mass of epothilone (M+H+) = 508.1 Da was present in the mass chromatogram. The product ions of 508.1 Da were found with the m/z values at 320.2 Da, and 420.2 Da, the typical MS2 fragments for standard epothilone B. This finding suggests that the fungal endophyte, G. lineata can be a potential source of epothilone B. J. Bangladesh Acad. Sci. 47(1); 91-99: June 2023